RELAPSED/REFRACTORY CHRONIC LYMPHOCYTIC LEUKEMIA: CHEMOIMMUNOTHERAPY, TREATMENT UNTIL PROGRESSION WITH MECHANISM-DRIVEN AGENTS OR FINITE-DURATION THERAPY? - Antonio Cuneo; Robin Foà (Mediterranean Journal of Hematology and Infectious Diseases)
Treatment of relapsed/refractory (R/R) chronic lymphocytic leukemia (CLL) has dramatically improved thanks to the development of mechanism-driven agents including drugs that inhibit kinases in the BCR pathway or BCL2. The treating physician has now the opportunity to decide i) which patient can be still offered chemoimmunotherapy as salvage treatment, ii) which patient is a candidate to receiving at relapse continuous treatment with ibrutinib, idelalisib and rituximab or venetoclax and iii) which patient may benefit from a fixed-duration treatment using the BCL2 antagonist venetoclax in association with rituximab.